Modification of Carbon Felt With Carbon Nanotubes as Electrodes for Microbial Fuel Cells - Nur Fadilah Kahfi; Muhammad Muhibuddin Mufqi (Eduvest - Journal of Universal Studies, 2026)
Microbial Fuel Cell as an alternative energy device that produces electrical energy. Microbial Fuel Cell is a device that can convert energy in organic matter into electrical energy using microorganisms that carry out metabolism as a catalyst. One of the electrodes, the anode, plays an important role as an electron acceptor in a microbial fuel cell. The anode used can be improved the resulting performance by modifying it using other materials. Therefore, in this study, variations of the anode of Carbon Felt modified by Carbon Nanotubes were used in the Single Chamber Microbial Fuel Cell. From the CF, CF/CNT1, CF/CNT2 and CF/CNT3 anodes used in this study, data on the CF/CNT2 anode showed the most optimal among other anodes with a sheet resistivity value of 14677.5 ± 2538.69 Ω/sq, the average voltage is 0.1228 V, the value of Maximum Power Density (DTM) is 42.45 mW/m2 at an average current density of 246.21 mA/m2. And the activity of microorganisms achieved by the CF/CNT2 anode is that it can oxidize glucose up to 96.13% and produce a biofilm mass of 0.255 ± 0.007 g. Then the concentration of CNT added to the CF anode will affect the electrical energy produced.